2000
DOI: 10.1038/sj.jea.7500078
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide storage and use patterns in Minnesota households with children

Abstract: As part of the National Human Exposure Assessment Survey ( NHEXAS ) , residential pesticide storage and use patterns were evaluated in a population -based sample of Minnesota households with children aged 3 ± 13. In -home interviews and inventories were conducted to identify pesticide products stored and used in and around 308 households. This statistically based sample represents more than 49,000 urban and rural households in the census tracts sampled. More than 850 unique products were identified using Envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
2
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 6 publications
2
63
2
2
Order By: Relevance
“…Even though inner-city census tracts were oversampled and the study population reflected the racial, and ethnic makeup of the census tracts as of 1990, the MNCPES sample had comparatively less geographic, racial, and ethnic diversity. A previous analysis has shown that the phone list used to recruit MNCPES subjects resulted in a study population with incomes approximately 40% greater than the median for the census tracts sampled (Adgate et al, 2000b).…”
Section: Discussionmentioning
confidence: 99%
“…Even though inner-city census tracts were oversampled and the study population reflected the racial, and ethnic makeup of the census tracts as of 1990, the MNCPES sample had comparatively less geographic, racial, and ethnic diversity. A previous analysis has shown that the phone list used to recruit MNCPES subjects resulted in a study population with incomes approximately 40% greater than the median for the census tracts sampled (Adgate et al, 2000b).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Savage et al (1981) reported that in the EPA region IX where California is located, 82.5% and 62.2% of households had ever used pesticides in the house and yard respectively, during late 1970s. Adgate et al (2000) collected residential pesticide inventory data in 1997 from households with children age 3-12 years in Minnesota, and reported a comparable prevalence of pesticide use for 88% of households during the past year. A study conducted in Detroit, Iowa, Los Angeles, and Seattle by Colt et al (2004) found that 94.3% of subjects had ever used insecticides in or around their residences.…”
Section: Comparison With Existing Studiesmentioning
confidence: 99%
“…Several nationaland regional-scale studies have been conducted, demonstrating that up to 90% of US households used pesticides in their house, garden, or yard, and more than half of the products applied were insecticides (Savage et al, 1981;Davis et al, 1992;Whitmore et al, 1994;Adgate et al, 2000;Colt et al, 2004). However, estimating human exposures from residential insecticide applications has been a challenge because of the lack of detailed information on the manner and patterns of applications and exposure related behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…A subsample of 335 residences was contacted by interviewers, who successfully completed screening procedures in 294 (88% ) residences within the 10± 12 day limit required to select monitoring participants. Phase 2 procedures were completed subsequently in 14 additional residences, for a total of 308 residences with completed screening questionnaires and product inventories (as described in Adgate et al, 2000 ). Completed baseline questionnaires were obtained for 173 (95% ) of the 183 households selected for follow -up, but only 159 ( 92% of 173) were available for monitoring during designated sampling weeks.…”
Section: Implementing the Study Designmentioning
confidence: 99%